Edukasi Pencegahan Anemia Melalui Gerakan Kepatuhan Konsumsi Tablet Tambah Darah (TTD) pada Remaja Putri di SMPN 4 Kediri Tabanan - Kadek Primadewi; Putu Adi Cahya Dewi (Health Care : Journal of Community Service, 2026)
Background: Anemia among adolescent girls is a significant public health problem that can adversely affect growth, learning concentration, productivity, and future reproductive health. Preventive efforts include health education and the regular consumption of Iron and Folic Acid (IFA) tablets; however, adherence remains suboptimal due to limited knowledge about anemia and the benefits of iron supplementation. Objective: To analyze the effect of anemia prevention education combined with an Iron and Folic Acid (IFA) tablet adherence campaign on improving the knowledge of adolescent girls at SMPN 4 Kediri, Tabanan Regency. Methods: A one-group pretest-posttest design was conducted involving 60 adolescent girls. Knowledge was assessed using a structured questionnaire before and after the educational intervention, while hemoglobin levels were measured as an initial screening for anemia. Data were analyzed using the Wilcoxon signed-rank test. Results: The mean knowledge score increased from 49.00 ± 5.43 before the intervention to 88.00 ± 4.80 after the intervention (p < 0.001), with a mean improvement of 39.00 ± 7.30 points. The mean hemoglobin level was 14.22 ± 1.60 g/dL, and the majority of participants were not anemic. Conclusion: Anemia prevention education combined with an IFA tablet adherence campaign effectively improved the knowledge of adolescent girls and has the potential to be integrated into the School Health Unit (UKS) program.